(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The current thesis is intended to analyze cultural aspects of English and Uzbek proverbs expressing the theme of friendship. The research further enumerates differences and similarities between English and Uzbek cultures with the help of proverbs used in verbal and non-verbal communication. The author uses comparative-cultural analysis, componential analysis method to accomplish the tasks of the research. Within the thesis, proverbs are also defined as a unit of parameiology as well as linguoculturology.